The University in Public Service: Some Reflections - Campbell, Duncan D. (Canadian Journal of Higher Education, 1977)
University public service, which takes a variety of forms, criticism and extension among them, is the least well rewarded of the institution's principal functions. Yet, of all organ- izations in society, the university has a special responsibility to identify social problems and to help resolve them. It is proposed that Canadian universities ought now to take the initiative, in consultation with leaders in both government and the-community, towards determining through what mechanisms publicly-provided university resources can most effectively be deployed in a public service thrust towards the improvement of the quality of Canadian life.